2018
DOI: 10.7717/peerj.4996
|View full text |Cite
|
Sign up to set email alerts
|

Sorption to soil, biochar and compost: is prediction to multicomponent mixtures possible based on single sorbent measurements?

Abstract: Amendment with biochar and/or compost has been proposed as a strategy to remediate soil contaminated with low levels of polycyclic aromatic hydrocarbons. The strong sorption potential of biochar can help sequestering contaminants while the compost may promote their degradation. An improved understanding of how sorption evolves upon soil amendment is an essential step towards the implementation of the approach. The present study reports on the sorption of pyrene to two soils, four biochars and one compost. Deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We caution here that results on the practical efficacy of biochar have been mixed: although biochar amendments in soil columns have been shown to capture highly mobile compounds including PFOA, other studies have shown less strong results . In part, these different results may be related to the properties of individual biochars, considering that the specific surface area, total pore volume, aromaticity, and polarity of biochars are important for contaminant sorption. , The performance of biochars in systems with soil and compost may also be weaker than would be predicted for biochar alone due to surface and pore blockages on the biochar and due to nonlinear contaminant sorption to biochar; our results do not account for either of these processes and so may overpredict capture. The findings that suggest bioretention supplemented with biochar can effectively capture highly mobile substances (such as PFOA) should therefore be viewed as preliminary, and we recommend validating these results with column- and field-scale experiments using authentic bioretention soils.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We caution here that results on the practical efficacy of biochar have been mixed: although biochar amendments in soil columns have been shown to capture highly mobile compounds including PFOA, other studies have shown less strong results . In part, these different results may be related to the properties of individual biochars, considering that the specific surface area, total pore volume, aromaticity, and polarity of biochars are important for contaminant sorption. , The performance of biochars in systems with soil and compost may also be weaker than would be predicted for biochar alone due to surface and pore blockages on the biochar and due to nonlinear contaminant sorption to biochar; our results do not account for either of these processes and so may overpredict capture. The findings that suggest bioretention supplemented with biochar can effectively capture highly mobile substances (such as PFOA) should therefore be viewed as preliminary, and we recommend validating these results with column- and field-scale experiments using authentic bioretention soils.…”
Section: Resultsmentioning
confidence: 92%
“…We then added the K d,amendment term to the organic carbon sorption term already present in the model. We note that this portion of the model has not been calibrated to or evaluated against experimental data, that we assumed amendments follow a linear sorption isotherm, and that the sorption provided by amendments is additive with sorption to organic carbon. , We therefore caution that results for amended bioretention systems have considerably greater uncertainty than for unamended systems, but still provide an indication of how additional sorptive materials would impact contaminant removal.…”
Section: Methodsmentioning
confidence: 99%
“…28 It has previously been demonstrated that batch and POM methods can be used as complementary methods. 32,33 The samples were equilibrated for 24 hours following a similar sample preparation to that described above but without adding any POM sheets, then centrifuged at 1000 g for 40 minutes and 30 mL of the supernatant was collected, which was then extracted three times with hexane following the addition of the internal standard (Pyr-d10).…”
Section: Sorption Experimentsmentioning
confidence: 99%
“…Biochar is a carbon-rich residue produced by the incomplete pyrolysis of biomass, 1,2 which is widely present in soil and generates potential benets for carbon sequestration, soil fertility, and immobilization and stabilization of hazardous chemicals, [3][4][5][6] due to its distinctive physicochemical characteristics, namely, large specic surface area (SSA), abundant porous structure, multifunctional groups, and strong adsorption capacity. [7][8][9][10] Inevitably, these vital characteristics of biochar can be altered once applied to the soil environment via shortterm or long-term physical, chemical, and biological processes, including natural aging, articial oxidation, and additional interactions with soil components, such as dissolved organic matter and minerals, [11][12][13][14] which, in turn, are likely to affect the adsorption behavior of contaminants, as well as their ultimate transport, fate, and bioavailability in soil. 15 In particular, studies involving the application of biochar for the immobilization of organic compounds in soil have been extensively reported.…”
Section: Introductionmentioning
confidence: 99%